2019
DOI: 10.1111/cid.12740
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal ridge augmentation with guided bone regeneration using particulate xenogenic bone substitutes with or without autogenous block grafts: A randomized controlled trial

Abstract: Background: To evaluate dimensional bone alterations following horizontal ridge augmentation using guided bone regeneration (GBR) with or without autogenous block graft (ABG) for the rehabilitation of atrophic jaws with dental implants.Materials and Methods: Forty-two patients, with 42 severe horizontal bone atrophy sites in the maxilla or mandible were randomly assigned to two groups: ABG or GBR. The ABG group received a combination of ABG with particulate xenograft, covered by a collagen membrane, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 42 publications
4
68
2
3
Order By: Relevance
“…While one study treated all minor wound dehiscences immediately with a PRGF membrane [31], another study treated all wound dehiscences with an initial course of systemic amoxicillin and clavulanic acid for 10 days and only proceeded to graft a dehisced site with a free gingival graft at the fifth week after surgery due to nonresolution [34]. One study reported late complications emerging only 3 to 4 months after the initial GBR, and they were treated with 0.5% chlorhexidine topical gel application, 0.12% chlorhexidine rinse, and a 1 week course of amoxicillin and clavulanic acid [29]. Minor infections such as suppuration were treated either only with systemic antibiotics [34] or with the addition of a chlorhexidine mouth rinse [16].…”
Section: Management Of Post-surgical Complicationsmentioning
confidence: 99%
“…While one study treated all minor wound dehiscences immediately with a PRGF membrane [31], another study treated all wound dehiscences with an initial course of systemic amoxicillin and clavulanic acid for 10 days and only proceeded to graft a dehisced site with a free gingival graft at the fifth week after surgery due to nonresolution [34]. One study reported late complications emerging only 3 to 4 months after the initial GBR, and they were treated with 0.5% chlorhexidine topical gel application, 0.12% chlorhexidine rinse, and a 1 week course of amoxicillin and clavulanic acid [29]. Minor infections such as suppuration were treated either only with systemic antibiotics [34] or with the addition of a chlorhexidine mouth rinse [16].…”
Section: Management Of Post-surgical Complicationsmentioning
confidence: 99%
“…Monje et al adopted iliac crest for horizontal bone augmentation but found out the donor site morbidity might cause patients unable to move freely, which limited its application in clinic . Similarly, Mendoza‐Azpur et al reported a randomized clinical trial utilizing chin bone ring to augment the anterior site, with the limitation of secondary surgical site and occurrence of the accompanying complications such as infection and paraesthesia of chin due to the incisal nerve injury . With the rapid progress of horizontal bone augmentation, several novel techniques have arisen in the last decade to compensate for the shortcomings of causing further stress concentration by creating favorable three‐dimensional space regarding bony walls as to realize desired augmented effect.…”
Section: Discussionmentioning
confidence: 99%
“…The so‐called bone ring technique, as using a ring‐shaped autogenous bone block, has emerged recently and been documented in several medical records showing excellent outcomes for the dimensional bone augmentation . Nevertheless, most of the reports only emphasizes on the vertical augmentation and the existing proposal for horizontal bone augmentation is lack of investigation on the stability of the biomaterials and reflects drawbacks such as aggravating intraoperative pain due to the secondary surgical site and occurrence of the accompanying complications such as infection and paraesthesia of chin due to the incisal nerve injury …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used anorganic bovine-derived bone mineral because is one of the most well-documented biomaterials and we mixed it with particulate freeze-dried bone allograft [ 11 ] to replace the autologous component. We took into consideration the fact that after a healing period of 9–10 months, the combination of deproteinized bovine bone mineral (DBBM) and a collagen membrane is an effective treatment option for horizontal bone augmentation before implant placement [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%